COVID-19 vaccination attitudes, perceptions, and side effect experiences in Malaysia: do age, gender, and vaccine type matter? - Elnaem, Mohamed Hassan Abdelaziz; Mohd Taufek, Nor Hidayah; Ab Rahman, Norny Syafinaz; Nazar, Nor Ilyani; Zin, Che Suraya; Nuffer, Wesley; Turner, Christopher John (MDPI, 2021)
This study aimed to investigate the attitudes, perceptions, and experiences of side effects with the COVID-19 vaccines in Malaysia among participants in the National Vaccination Program. A cross-sectional survey was conducted among a sample of vaccine-eligible and vaccinated individuals in Malaysia between May and July 2021. A total of 428 respondents completed the survey. A vast majority (98.6%) of the respondents had registered to be vaccinated. Twenty participants (4.7%) expressed concerns about either registering or receiving the COVID-19 vaccination, mainly due to their uncertainty of vaccine safety. Approximately 77.5% received their vaccinations. Of them, 76.8% had experienced vaccine-related side effects. About 40% of the side effects occurred more with the second dose, particularly those who received the Pfizer-BioNTech vaccine (p < 0.001). Pain at the injection site (61.1%) and tiredness (48.8%) were the most reported side effects. Compared to those aged ≥60 years, all age groups were more likely to exhibit vaccine-related side effects; meanwhile, males (OR: 0.51, 95% CI: 0.27–0.93) were less likely to experience side effects than females. Those who received the Sinovac vaccine were at lower risk of experiencing side effects (OR: 0.08, 95% CI: 0.03–0.22) and were more likely to report fewer side effects than Pfizer-BioNTech (p = 0.012) and Oxford-AstraZeneca groups (p= 0.001). The overall attitudes toward the COVID-19 vaccination program were positive. Several differences in the experiences of vaccine-related side effects, in terms of prevalence and numbers, were attributed to age, gender, and received vaccine type.